Media and metamedia management - Freire, Francisco Campos (Springer, 2017)
Media and Metamedia Management has contributions from seven prestigious experts, who offer their expertise and the view from their vantage point on communication, journalism, advertising, audiovisual, and corporate, political, and digital communication, paying special attention to the role of new technologies, the Internet and social networks, also from an ethics and legal dimension. A total of 118 authors belonging to 31 universities from Spain, Portugal, England and Ecuador have contributed to this book edited, coordinated and introduced by professors Francisco Campos-Freire and Xosé López-García, from the University of Santiago de Compostela, José Rúas-Araújo, from the University of Vigo, and Valentín A. Martínez-Fernández, from the University of A Coruña. Readers may also enjoy 66 articles, grouped into diverse chapters, on Journalism and cyberjournalism, audiovisual sector and media economy, corporate and institutional communication, and new media and metamedia.
Keywords: Digital media.; Online journalism.; elektronické knihy; electronic books